Benzenesulfonyl Chlorides: Alternative Coupling Partners for Regiocontrolled Palladium-Catalyzed Direct Desulfitative 5-Arylation of Furans - Beladhria, Anissa; Yuan, Kedong; Ben Ammar, Hamed; Soulé, Jean-Francois; Ben Salem, Ridha; Doucet, Henri (Synthesis, 2014)
The reactivity of furan derivatives in palladium-catalyzed desulfitative arylation was studied. Alkyl-substituted furan derivatives were successfully coupled with a variety of benzenesulfonyl chlorides using a phosphine-free catalyst; regioselective arylation at C5 of the furan was observed in all cases. This reaction tolerates a wide variety of substituents on the benzenesulfonyl derivative. It should be noted that even bromo- and iodobenzenesulfonyl chlorides were successfully coupled with furan derivatives without cleavage of the C–Br or C–I bonds, thus allowing further transformations. The use of these reactants demonstrates the potential of benzenesulfonyl chlorides as coupling partners to access to functionalized 5-arylfurans.
Keywords: palladium; C–H bond activation; furans; benzenesulfonyl chlorides; arylation